The Use Of Tiktok Application: The Impact On Efl Learners’ Speaking - Elma Tiyana; Selamet Riadi Jaelani; Siti Ayu Surayya; Muhammad Husnu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aimed to determine the effectiveness of using TikTok application in improving speaking skill for EFL learners. The research design employs pre-experimental research with the sample of 25 students. The technique data collection was done by administering pre-test and post-test. This research used descriptive statistic Paired Sample T-Test to analyze the data. The mean score of pre-test was 46.6 and 71.4 for post-test. Based on the statistical analysis, it showed that the use of TikTok application give a good impact for the students speaking skill because the mean score of post-test was higher than pre-test. In testing hypothesis, it was found that the significance value of the result of TikTok application thought self-introduction was 0.00 lower than 0.05, so the hypothesis was accepted. Additionally, some improvements were seen after the treatment such as “I em” to be “I am”, “lipe” to be “live” and other vocabulary items. In conclusion, TikTok application was significantly effective in improving speaking skill for EFL learners at X grade in SMK Unwanul Falah NWDI Paok Lombok.